A systematic review of studies of eye movement desensitization and reprocessing (EMDR) therapy for post-traumatic stress disorder from 2017 to 2021 documented in the Saudi digital library - Almehdar, Areej Salem (Journal of Educational and Psychological Sciences, 2023)
The results from scientific research over the past three decades have proven that Eye Movement desensitization and reprocessing EMDR, is an effective treatment in cases of post-traumatic stress disorder and is also effective in relieving the symptoms of many other psychological disorders. Due to the scarcity of published studies on the effectiveness of this treatment in Arabic, the current study came to fill this research gap, and to conduct a systematic review that reveals the most prominent features of research in trauma treatment with eye movement and desensitization and re-processing (EMDR) as reflected in the Saudi Digital Library in the period from 2017 to 2021 AD. The research relied on using the method of systematic literature review. This review concluded with 17 papers written in English and two papers written in Arabic. These studies are varied in their methods and the target groups. The systematic review reached a clear understanding of the most prominent current and future trends and topics that are being dealt with in EMDR trauma treatment studies. The recommendations indicated the urgent need for more studies and research in Arabic culture that prove the effectiveness of eye movement desensitization and reprocessing (EMDR) therapy for post-traumatic stress disorder with different clinical groups in Arabic culture.
Keywords: Eye Movement and Desensitization and Reprocessing; Post-Traumatic Stress Disorder; Medical psychotherapy; Systematic Review